A detailed study of the variations found in the chrysalises of Aglais caschmirensis Kollar, 1844 (Lepidoptera: Papilionoidea, Nymphalidae) - Lovish Garlani (SHILAP)
Ninety larvae of Aglais caschmirensis Kollar, 1844 were studied in September 2022 in Dharamshala, Himachal Pradesh, India. All the larvae were fed on the host plant Urtica dioica. The study reveals that the larvae of Aglais caschmirensis Kollar, 1844 produce chrysalises of four different colors i.e., Golden, Red, Green, and Brown. This study found that Golden is the most dominant color of chrysalises with the highest survival rate while Green is the rarest color in chrysalises. The survival rate of Brown colored chrysalises is moderate while interestingly all the red chrysalises were affected by parasitoids and did not survive which shows that Parasitoidism is somehow responsible for phenotypic variations in the chrysalises of Aglais caschmirensis Kollar, 1844.